2022
DOI: 10.1111/imm.13566
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin‐derived chimeric peptide (LFch) strongly boosts TGFβ1‐mediated inducible Treg differentiation possibly through downregulating TCR/CD28 signalling

Abstract: We recently reported that lactoferrin (LF) induces Foxp3 + Treg differentiation through binding to TGFβ receptor III (TβRIII), and this activity was further enhanced by TGFβ1. Generally, a low T-cell receptor (TCR) signal strength is favourable for Foxp3 + Treg differentiation. In the present study, we explored the effect of lactoferrin chimera (LFch, and lactoferrampin [aa 265-284]), along with TGFβ1 on Foxp3 + Treg differentiation. LFch alone did not induce Foxp3 expression, yet LFch dramatically enhanced TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In the case of iTregs, it was shown that low doses of Ag or polyclonal TCR activators induce Foxp3 expression, whereas high doses of these stimuli ameliorate Foxp3 upregulation ( 9 ). Consistently, we and others have shown that inhibition of downstream mediators of TCR/CD28 signaling, such as PI3K, protein kinase B (Akt), and mTOR, significantly augments TGF-β1–induced Foxp3 expression ( 10 11 ). However, it is not known how TCR/CD28 signaling intensities (high or low) affect TGF-β-mediated Foxp3 expression in the presence of RA and LF.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the case of iTregs, it was shown that low doses of Ag or polyclonal TCR activators induce Foxp3 expression, whereas high doses of these stimuli ameliorate Foxp3 upregulation ( 9 ). Consistently, we and others have shown that inhibition of downstream mediators of TCR/CD28 signaling, such as PI3K, protein kinase B (Akt), and mTOR, significantly augments TGF-β1–induced Foxp3 expression ( 10 11 ). However, it is not known how TCR/CD28 signaling intensities (high or low) affect TGF-β-mediated Foxp3 expression in the presence of RA and LF.…”
Section: Introductionsupporting
confidence: 82%
“…However, the mechanism by which this combination might cause such synergistic iTreg generation remains unknown. It is well established that TGF-β/Smad3–dependent signaling induces Foxp3 + Treg differentiation ( 3 4 ), and TGF-β1–mediated iTreg generation is further enhanced by LF and its peptides ( 7 11 ). These studies reveal that LF promotes Foxp3 upregulation through two mechanisms: by phosphorylating Smad3 through activation of membrane-bound TGF-β and attenuating TCR/CD28 signaling, both of which occur via TGF-β type III receptor.…”
Section: Discussionmentioning
confidence: 99%